The spiritual and mental health assessment of social workers working for Internally Displaced Persons during Covid-19 in Myanmar - Saw Ye Win Thu; Hsiu-Ching Chen (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
This study utilizes the spiritual assessment viewpoint to analyze the spirituality of social workers who are working for Internally Displaced Persons (IDPs) in Kachin and Northern Shan State, Myanmar where the working situation is stressful, and security is not guaranteed. The data is collected online during the pandemic and military coup, in April 2022. It is a quantitative research assessment and the form of Spirituality Assessment of Social Workers Working for IDPs (SASWWIDPs) is designed as three dimensions of SASWWIDPs: Healthy self-awareness (HSA), healthy relationship (HR), and healthy feeling (HF). The accumulated data is interpreted using SPSS 22.0 for statistical analysis. Most of the participants are female (66%) and 34% are male. The results of the three dimensions of the SASWWIDPs are different from their social characteristics: in gender, females’ HF in self-care and managing stress is higher than males (t=-3.21**). In terms of religion/faith, the group Buddhism’s HF is higher than Christianity on the benefits of religion in managing stress (t=-2.833**). Regarding working years, people who have been working for 2 years have a more positive mindset on their work than those for 3 years above in HSA (t=2.918**); in terms of age, there is no difference among the different age groups. However, both groups agree the role of friends and families is vital to overcoming challenges and stress.